MEDIA LITERACY: DEEPFAKES AND TEENAGERS EXPERIENCES IN HOAX PRODUCTION - Pratiwi, Yuly Rahmi; Aslinda, Cutra; Fitri, Amelia (Universitas prof. Dr. Moestopo (Beragama), 2024)
Communication technology facilitates information dissemination, but it also leads to information pollution. The youth, being the largest users, lacks filtering skills, making them vulnerable to false information. Teenagers in Pekanbaru City, who frequently use the internet, even though they are used to using the internet to produce and disseminate information, they may not realize false information is being spread. This research aims to look at the deep-fake experience among Pekanbaru teenagers. The method used in this research is qualitative with data collection techniques, namely interviews. The results of this study show that the media literacy experience of Pekanbaru teenagers in using the media is not for hoaxes and is at the level of technical skills of teenagers at an advanced level, critical understanding at a medium level, and communicative abilities at a medium level. In environmental factors, teenagers get it from peers and use deepfake not to produce hoaxes.